2021
DOI: 10.1001/jamanetworkopen.2021.33384
|View full text |Cite
|
Sign up to set email alerts
|

Association of Individual and Familial History of Correctional Control With Health Outcomes of Patients in a Primary Care Center

Abstract: IMPORTANCEResearch has shown that experiences of incarceration, probation, and parole are associated with worse health outcomes for incarcerated individuals and their families. OBJECTIVES To quantify the proportion of patients in an urban primary care clinic with an individual or family history of incarceration, probation, and/or parole and to evaluate how correctional control is associated with subjective and objective health outcomes. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional, mixed-methods stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…For instance, studies of clients receiving primary care in urban areas have shown that up to 50% have been arrested, incarcerated, or have a family member who has been arrested or incarcerated. 21 As a result, our group has recently advocated to incorporate questions about involvement in correctional control into standard social determinants of health screening questionnaires in clinical set- tings. 22 Screening for any social determinant of health, including correctional control, is best done using a team-based approach such as an MLP, where there are professionals with the expertise to respond to unmet needs.…”
Section: Integrating Criminal Legal Needs Into the Medical-legal Part...mentioning
confidence: 99%
“…For instance, studies of clients receiving primary care in urban areas have shown that up to 50% have been arrested, incarcerated, or have a family member who has been arrested or incarcerated. 21 As a result, our group has recently advocated to incorporate questions about involvement in correctional control into standard social determinants of health screening questionnaires in clinical set- tings. 22 Screening for any social determinant of health, including correctional control, is best done using a team-based approach such as an MLP, where there are professionals with the expertise to respond to unmet needs.…”
Section: Integrating Criminal Legal Needs Into the Medical-legal Part...mentioning
confidence: 99%